Fluorescein-based SynNotch adaptors for regulating gene expression responses to diverse extracellular and matrix-based cues - Jeremy C. Tran; Christopher J. Kuffner; Alexander M. Marzilli; Ryan Emily Miller; Zachary E. Silfen; Jeffrey B. McMahan; D. Christopher Sloas; Christopher S. Chen; John T. Ngo (Nature Communications)
Abstract Synthetic Notch (SynNotch) receptors function like natural Notch proteins and can be used to install customized sense-and-respond capabilities into mammalian cells. Here, we introduce an adaptor-based strategy for regulating SynNotch activity via fluorescein isomers and analogs. Using an optimized fluorescein-binding SynNotch receptor, we describe ways to chemically control SynNotch signaling, including an approach based on a bio-orthogonal chemical ligation and a spatially controllable strategy via the photo-patterned uncaging of an o-nitrobenzyl-caged fluorescein conjugate. We further show that fluorescein-conjugated extracellular matrix (ECM)-binding peptides can be used to regulate SynNotch activity depending on the folding state of collagen-based ECM networks. To demonstrate the utility of these tools, we apply them to activate dose-dependent gene expression responses and to induce myogenic-like phenotypes in multipotent fibroblasts with spatiotemporal and microenvironmental control. Overall, we introduce an optimized fluorescein-binding SynNotch as a versatile tool for regulating transcriptional responses to ligands based on the clinically-approved fluorescein dye.